IMPLEMENTASI AKUNTANSI BERBASIS AKRUAL DALAM LAPORAN KEUANGAN PEMERINTAH: STUDI TINJAUAN LITERATUR [IMPLEMENTATION OF ACCRUAL-BASED ACCOUNTING IN GOVERNMENT FINANCIAL REPORTS: A LITERATURE REVIEW STUDY] - Adinda Naya Salsabilla; Ardhina Dwi Sabtara; Divyana Aprila Daung Salsabilla; Rinny Meidiyustiani (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
This study aims to analyze the effect of the implementation of accrual-based accounting on the quality of government financial reports, with Government Accounting Standards (SAP) as a reference framework. The implementation of accrual-based accounting is considered to be able to increase transparency and accountability in state financial management through the recognition of income and expenses when they occur, not when cash is received or recorded. However, the effectiveness of this implementation is highly dependent on the competence of the human resources involved in the preparation of financial reports. This study uses a descriptive approach where researchers search for articles and journals from various databases such as Google Scholar, DOAJ, and accredited campus journal portals such as Garuda and Sinta with the criteria of being published in the period 2020-2025, with the conclusion that the accrual-based accounting recording method can improve the quality of government financial report preparation because it can predict the future that reflects economic reality.